Introduction to Frustrated Magnetism Materials, Experiments, Theory - Lacroix, Claudine; Mendels, Philippe; Mila, Frédéric; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
The field of Highly Frustrated Magnetism has developed and expanded considerably over the last 15 years. Originating with canonical geometric frustration of interactions, it today extends over other phenomena with many degrees of freedom, including magneto-elastic couplings, orbital degrees of freedom, dilution effects, and electron doping. It is also demonstrated that the concept of frustration impacts many other fields in physics beyond magnetism. This book represents a state-of-the-art review aimed at a broad audience with tutorial chapters and more topical ones, which encompass solid-state chemistry as well as experimental and theoretical physics.
First Part: Basic concepts in frustrated magnetism -- Thermal and Quantum Fluctuations in Frustrated Magnets -- Quantum Spin Liquids -- Second Part: Probing frustrated magnets -- Thermodynamic Measurements -- Neutron scattering -- Resonance experiments (ESR, NMR, µ-SR) -- Light experiments -- Third Part: Frustrated systems -- Synthesis and crystal growth of frustrated magnets -- Spinels -- Pyrochlores -- Kagome -- Fourth part: Specific effects in frustrated magnets -- Magnetization plateaux -- Lattice instabilities -- Spin ice -- Fifth part: Advanced Theorical Methods in Frustrated Magnetism -- Large N approaches and Schwinger bosons -- Variational Monte-Carlo and Projected Wavefunctions -- Quantum Dimer Models -- Numerical Simulations of Frustrated Quantum Magnets -- Exactly Soluble Models of Frustrated Quantum Magnetism -- Strong-coupling Expansions -- Sixth part: Related topics -- Biquadratic interactions and ring exchange -- Mobile Holes in Frustrated Quantum Magnets -- Metallic and Superconducting Doped Frustrated Magnets -- Orbital Degeneracy.
Keywords: Magnetism; Magnetic materials; Structural materials; Engineering; Magnetism, Magnetic Materials; Structural Materials; Engineering, general